Model Integratif Pendidikan Agama Islam Multikultural dalam Meningkatkan Kompetensi Sosial Mahasiswa - Mannuhung, Suparman; Hanafie Das, St. Wardah (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2026)
This study aims to analyze the implementation of an integrative learning model based on multicultural values in Islamic Religious Education (PAI) and its contribution to enhancing the social competence of students at Andi Djemma University. The research employed a descriptive qualitative approach with a case study design, involving one PAI lecturer and ten students from Bugis, Toraja, and Luwu ethnic backgrounds as informants. Data were collected through in-depth interviews, participatory observations, and document analysis, and were analyzed using Miles and Huberman’s thematic analysis technique with source triangulation to ensure data validity. The findings reveal that the application of the multicultural integrative learning model through interactive lectures, cross-ethnic discussions, and socio-religious reflections successfully created an inclusive and dialogical learning atmosphere. The integration of values such as tolerance, empathy, equality, and social justice into the learning process strengthened students’ communication skills, collaboration, and social sensitivity. Furthermore, the model contributed to reinforcing religious moderation, fostering more open-minded attitudes among students, and promoting respect for diversity. The study also identified several challenges, including limited instructional time, learning materials that were not yet fully contextual, and hierarchical cultural patterns that restricted the active participation of some students. This research concludes that the multicultural integrative PAI model is an effective approach for developing students’ social competence while simultaneously strengthening moderate and contextually grounded Islamic character. The findings are expected to serve as a foundation for developing multicultural-based PAI curricula in public universities.